2001
DOI: 10.1515/cclm.2001.057
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases: Potential Therapeutic Target in Spinal Cord Injury

Abstract: Mediators of extracellular matrix proteins degradation, the matrix metalloproteinases (MMPs), involved in inflammation as well as facilitation of process outgrowth of oligodendrocytes are interesting targets for neural repair. Recent data reported their activation after seizures, cerebral ischemia and spinal cord injury. The present study was designed to localize at cellular level the gelatinase activity by in situ zymography in a rat spinal cord contusion model. The kinetic of gelatinase activation was monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Moreover, the restricted axonal outgrowth observed after application of MMP‐2 inhibitors or morpholinos suggested a functional involvement of MMP‐2 in RGC axonal outgrowth (Janssens et al, ; Gaublomme et al, ). In adult mammals in which regeneration was triggered after injury of the spinal cord or optic nerve, a positive correlation between gelatinase activity and axonal regeneration has been observed, although causality was not demonstrated (Duchossoy et al, ; Ahmed et al, ). Strikingly, however, MMP‐2 seemed mainly localized around the scar tissue itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the restricted axonal outgrowth observed after application of MMP‐2 inhibitors or morpholinos suggested a functional involvement of MMP‐2 in RGC axonal outgrowth (Janssens et al, ; Gaublomme et al, ). In adult mammals in which regeneration was triggered after injury of the spinal cord or optic nerve, a positive correlation between gelatinase activity and axonal regeneration has been observed, although causality was not demonstrated (Duchossoy et al, ; Ahmed et al, ). Strikingly, however, MMP‐2 seemed mainly localized around the scar tissue itself.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, a vast amount of studies implicate MMPs as key players in the degradation of inhibitory molecules around the injury site, thereby clearing the path for axons to regrow. For example, in adult rats, which were triggered to regenerate axons across the injury site of damaged spinal cords and optic nerves, gelatinase activity was strongly induced in the scar tissue, thus seemingly necessary to degrade the inhibitory environment (Duchossoy et al, ; Ahmed et al, ). Indeed, several independent studies identified MMP‐2 as a major proteinase able to reduce the glial scar through cleavage of chondroitin sulfate proteoglycans (CSPGs) (Hsu et al, ; Pastrana et al, ; Veeravalli et al, ; Filous et al, ).…”
mentioning
confidence: 99%
“…29 Fresh whole eyes with their eyelids and conjunctiva were embedded in a mixture of 75% (v) OCT compound (Sakura Finetek USA, Inc., Torrance, CA) and 25% (v) Immu-Mount (Thermo-Shandon, Pittsburgh, PA) and then frozen in liquid nitrogen. Ten-micrometer sections were cut using a cryostat (Leica, Wetzler, Germany) and stored at Ϫ80°C until use.…”
Section: In Situ Zymographymentioning
confidence: 99%
“…In situ zymography Frozen sections from the ventral prostates were subjected to in situ gelatin zymography as described (Duchossoy et al 2001). Air-dried sections were covered with 20 L of the substrate reaction mixture 50 mM Tris, pH 7.5, 5 mM CaCl 2 , 0.03% sodium azide containing 50 g/mL quenched Xuorescein-labeled DQ gelatin (EnzCheck, Molecular Probes, Eugene CA, USA) and incubated for 2 h at 37°C in a humid chamber.…”
Section: Western Blottingmentioning
confidence: 99%